The Impact of Antiretroviral Therapy on Liver Function Among Pregnant Women Living with HIV in Co-Existence with and Without Pre-Eclampsia - Kay-Lee E. Strauss; Wendy N. Phoswa; Kabelo Mokgalaboni (Viruses)
Pregnant women living with HIV (PWLWHIV) are at an increased risk of developing obstetrics complications such as pre-eclampsia (PE). Antiretroviral therapy (ART) remains the standard treatment for PWLWHIV and non-pregnant women. However, its use has been associated with adverse liver conditions, particularly hepatotoxicity, often marked by elevated liver enzymes (LEEs) as demonstrated by an increased aspartate transferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) in PWLWHIV on ART. Morever, there is limited evidence about the effect of ART on liver function among PWLWHIV and PE. Therefore, this review examines the pathogenesis of PE and the impact of ART on liver function in PWLWHIV with and without PE. With the evidence gathered in this review, it is still unclear whether liver dysfunctions in PWLWHIV in co-existence with orwithout PE result from HIV infection or ART administration or are exacerbated by the presence of PE. Among those without PE, there was an increase in liver enzymes, a decrease, and no effect in other studies in ART-treated PWLWHIV compared to the control group. Additionally, among those with PE, the impact of ART remains unclear due to contradicting results. The notable trend was that nevirapine was associated with a reduced risk of liver dysfunction among PWLWHIV without PE. Therefore, more studies are needed in this area, especially in HIV endemic regions, to understand the exact cause of liver dysfunction in this population. This knowledge is crucial for improving liver function and PE management among PWLWHIV.